The Health and Well-being of Female Labour Migrants from Nepal: A Qualitative Study of Stakeholders - Khatri, Rose; Teijlingen , Edwin van; Simkhada , Padam (Europasian Journal of Medical Sciences, 2021)
Female labour migration from the global south to the Middle East has increased in recent times. The rights and health of these women are often severely affected during and post migration. The aim of this study was to provide a clearer understanding of the process and context of female labour migration from Nepal. This included reasons for female labour migration, the risks, benefits, health impacts and measures to better support and protect women before, during and post migration. Data in this paper is based on semi-structured interviews conducted with ten key stakeholders (staff working with support organisations, policy-makers and researchers in the field) all with a professional interest in female labour migration from Nepal. It was found that government restrictions on female labour migrants working in the domestic sector increased undocumented migration through India, increasing the risk of trafficking and exploitation. Despite these risks, migration is attractive to many Nepalese women as it offers an opportunity to improve livelihood for them and their family. In addition, it can provide a ‘window to empowerment’. The study concludes that restricted migration, implemented in the name of protection, has undermined the rights, security and health of many Nepalese women. DOI: https://doi.org/10.46405/ejms.v3i2.384